Aplicação da água residuária das salinas no tratamento de efluente têxtil - Albuquerque, Liana Filgueira (2009)
The treatment of colored and alkaline effluent has been a challenge to the textile industry. An alternative to remove the colors of those effluents is applying magnesium chloride as a coagulant agent. The magnesium ion, in high pH, hydrolyzes itself, forming the magnesium hydroxide which has a large adsorptive area and positive electrostatic charges able to act as an efficient coagulant. The bittern wastewater from the salt industries has been studied as a potential font of this magnesium ion. Nowadays, this bittern wastewater is evicted into the sea, without any treatment or other use. This thesis has evaluated the potential of applying the wastewater from the salt industries in the treatment of dyeing effluent containing indigo dye and alkaline pH. All the experiments were made in jar tests simulating the chemical coagulation, flocculation and decantation steps ranging the pH and the concentration of magnesium ion. Were obtained removals between 96% and 76% for turbidity, apparent color, and true color, respectively, using 200mg/L Mg2+. The reduction of costs with acid, when were used the salt industries wastewater, comparing with Al2(SO4)3, was 62%. For the degradation of organic matter remaining in the clarified, around 900 mg/L, was applyed the advanced process of oxidation: photo-Fenton. The preliminary results showed 57% reduction in DOC. According to the results obtained, the salt industries wastewater can be applied, as coagulant, in the physical-chemical treatment of the denim dyeing wastewater, so it is not necessary a previous adjust of pH, efficiently and economically